58.2k views
3 votes
Use the quadratic formula to solve the equation: 2x^2-4x+1=0

User Dagronlund
by
4.9k points

1 Answer

4 votes

The quadratic formula is


x = (-b \pm √(b^2 - 4ac))/(2a)

In this problem, a = 2, b = -4, c = 1


x = (-(-4) \pm √((-4)^2 - 4(2)(1)))/(2(2))


x = (4 \pm √(16 - 8))/(4)


x = (4 \pm √(8))/(4)


x = (4 \pm 2√(2))/(4)


x = 1 \pm (√(2))/(2)

User Sharefa
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.